Szacowanie ryzyka powtórnej przestępczości w kontekście Evidence-Based Practice - Szwejka, Łukasz; Piasecka, Małgorzata (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The aim of this paper is to present the eﬀectiveness of correctional programmes, which were made in the context of what works. The usage of scientiﬁc knowledge in the ﬁeld of recidivism assessment is the main postulate of the what works movement. Based on scientiﬁc evidence, the R-N-R (Risk-Need-Responsivity) programme was constructed.
Keywords: praktyka oparta na dowodach; recydywa; ocena ryzyka / potrzeb